Performance evaluation of a solar powered air dryer for white oyster mushroom drying - Mustayen, A.G.M.B.; Rahman, M.M.; Mekhilef, Saad; Saidur, R. (Taylor & Francis, 2015)
In this paper, the performance of an efficient solar dryer was experimentally investigated and tested. The dryer was configured for harvesting maximum rate of solar radiation by having a longer drying period. The three axial flow fans provide the air inlet which can accelerate the drying rate. An electrical backup was also used for continuous drying process. Final moisture content and cabinet temperature (CT) were recorded and compared to the open sun drying and oven drying process. White oyster mushroom was dried at 50 degrees C to 60 degrees C and the desired moisture content of 7.97 has been achieved without affecting the product color. Activation energy, product output rate (POR), evaporation rate have been calculated. Shrinkage of drying mushroom was analyzed at different temperatures. The important climatic variables such as solar radiation, temperature and relative humidity are the main factors that affect the drying rate constant (k). Final output indicates that the quality of dried product in solar powered air dryer was competitive with the branded products available in the market. This drying system can be used for a wide range of agricultural products.